2009
DOI: 10.1084/jem.20091059
|View full text |Cite
|
Sign up to set email alerts
|

TPL-2 negatively regulates interferon-β production in macrophages and myeloid dendritic cells

Abstract: Stimulation of Toll-like receptors (TLRs) on macrophages and dendritic cells (DCs) by pathogen-derived products induces the production of cytokines, which play an important role in immune responses. Here, we investigated the role of the TPL-2 signaling pathway in TLR induction of interferon-β (IFN-β) and interleukin-10 (IL-10) in these cell types. It has previously been suggested that IFN-β and IL-10 are coordinately regulated after TLR stimulation. However, in the absence of TPL-2 signaling, lipopolysaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

36
183
3
5

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 150 publications
(228 citation statements)
references
References 43 publications
(97 reference statements)
36
183
3
5
Order By: Relevance
“…We next decided to determine how Cot/tpl2 regulates the expression of other genes involved in the macrophage response to LPS stimulation. In agreement with previous data [39,40], Cot/tpl2 repressed IFN-b and IL-12 p40 transcripts levels in LPS-activated macrophages (Supporting Information Fig. S4), furthermore LPS-stimulated Cot/tpl2 KO BMDMs showed enhanced IFN-g, CCL5 and CXCL-10 while decreased CXCL-1 mRNA expression levels versus their LPSstimulated WT counterparts (Supporting Information Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…We next decided to determine how Cot/tpl2 regulates the expression of other genes involved in the macrophage response to LPS stimulation. In agreement with previous data [39,40], Cot/tpl2 repressed IFN-b and IL-12 p40 transcripts levels in LPS-activated macrophages (Supporting Information Fig. S4), furthermore LPS-stimulated Cot/tpl2 KO BMDMs showed enhanced IFN-g, CCL5 and CXCL-10 while decreased CXCL-1 mRNA expression levels versus their LPSstimulated WT counterparts (Supporting Information Fig.…”
Section: Resultssupporting
confidence: 92%
“…2A). A similar JNK and p38a phosphorylation state was observed between WT and Cot/tpl2 KO BMDMs within the first 40 min following LPS stimulation, in accordance with earlier studies [17,36,39]. However, p38a and JNK phosphorylation were sustained for longer in LPS-stimulated Cot/tpl2 KO BMDMs versus WT BMDMs.…”
Section: Increased P38a and Jnk Phosphorylation And Impaired Ijba Recsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, LPS stimulation activates the MEK kinase activity of TPL-2 [33,34]. TPL-2 is also required for TLR2, TLR9 and TNF activation of ERK in macrophages [35][36][37] and CD40 activation of ERK in B cells [35]. In other cell types, the function of TPL-2 may not be restricted to the regulation of the ERK MAP kinase pathway.…”
Section: S125mentioning
confidence: 99%
“…The TPL-2 MAPK signaling pathway gives rise to a complex network of cytokine regulation. While it is crucial for promoting the processing of the secreted form of the proinflammatory cytokine TNF-a [28], recent work has shown that it induces the anti-inflammatory cytokine IL-10 and negatively controls the proinflammatory cytokines IL-12 and IFN-b in macrophages and myeloid DC [29].MAPK3 has also been reported to phosphorylate and activate CdGAP, which is a negative regulator of the Rho GTPase Cdc42 [30]. This GTPase is an important regulator of actin dynamics.…”
mentioning
confidence: 99%